The Berlin-Baghdad Express : The Ottoman Empire and Germany's Bid for World Power, 1898-1918 - Mcmeekin, Sean (London Penguin, Books, 2011)
Prior to the First World War, Germany sought the Ottoman Empire as an ally to create a jihad against the British. 'The Berlin-Baghdad Express' provides a fascinating account of Western interference in the Middle East and its lamentable results.
Include Map, Note, Bibliography and Index
Keywords: World War (1914-1918) -- Turkey -- Germany -- Islamic countries -- Diplomatic relations